(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Biotechnology has become a crucial tool in the production of meat products, offering innovative solutions to improve food safety, extend shelf life, and enhance nutritional value. The use of biotechnological methods, such as microbial fermentation, enzymatic processing, and cell-based meat production, has significantly transformed the meat industry. In Uzbekistan, the adoption of biotechnology in meat processing is still in its early stages, yet it holds great potential for improving food security and sustainability. This paper explores the prospects and limitations of biotechnology in meat production, analyzing its economic, technological, and regulatory implications. The study highlights the benefits of biotechnology in enhancing meat quality while addressing concerns related to consumer acceptance, ethical issues, and industrial implementation. By examining successful case studies and current trends, this research provides insights into the future role of biotechnology in Uzbekistan’s meat industry.